Serum type III procollagen, procollagen V, Tumor necrosis factor-α, interleukin-6 in liver cirrhosis after antiviral treatment: Serum PCⅢ, procollagen V TNF-α, IL-6 in cirrhosis - Li, Wei (Journal of Medical Biochemistry, 2025)
Objective: To look into the therapeutic impact of entecavir in combination with reduced glutathione on serum type III procollagen (PCⅢ), plasma procollagen V (IVC),Tumor necrosis factor-α, interleukin-6 in the treatment of hepatitis B complicated with alcoholic liver cirrhosis and the impact on nutritional status. Methods: The study included 92 patients with alcoholic liver cirrhosis complicating hepatitis B who were treated in our hospital between April 2022 and January 2024. The patients were randomized into two groups using a random number table method: group A, which included 46 patients, and group B, which included 46 patients who were in the experimental group. Patients in group A received treatment with 0.5 mg of entecavir per day, whereas those in group B received 0.5 mg of entecavir per day with 0.3 g of reduced glutathione 1-2 times per day. The treatment was continuous for 2 months.The BMI, TSF, AMC, PA, HB, and ALB were compared between the two groups, as were the clinical treatment outcomes for the two patient groups. The incidence of malnutrition was evaluated using a fully automatic biochemical analyzer, and the incidence of malnutrition was evaluated using SGA nutritional risk screening; The expression levels of inflammatory factors were detected by ELISA before and after treatment in the two groups. Liver function indicators were detected by immunoradiology to detect liver fibrosis indicators; A comparison was made between the two groups’ incidence of adverse responses. Result: Group B’s overall effective rate was 97.82%, higher than that of group A (76.08%); The degree of malnutrition decreased after therapy compared to before, and group B fared better than group A, the expression levels of BMI, TSF, AMC, PA, HB, ALB, TNF-α, CRP, IL-6, TBIL, AST, ALT, HA, PCⅢ and IVC in both groups were decreased than group A after treatment, and these in the group B were reduced than group A . Conclusion: Entecavir combined with reduced glutathione in the treatment of hepatitis B complicated with alcoholic liver cirrhosis can improve liver function, and the nutritional status of patients, reduce inflammatory indicators, and have high safety.